Food Traceability and Security in Supply Chain Using RFID Technology - Evizal .; Sri Listia Rosa; Siti Mariyam Shamsuddin; Eko Supriyanto; Wahyudi Sutopo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In recent year due to high demand of food product especially agricultural food then supplied from various countries or regions and lands. Some cases facing out such as on delivery, food safety and consumer care. Thus, agricultural food product safety, traceability and monitoring system is required for food product. In this paper propose a system for food traceability and security in supply chain using RFID technology, where a tag attached to every bucket or packet of food product as identification for product source, batch and expire date. Every process in supply chain of food product identified by RFID reader and scanning the tags then all scanned data send to centralized database for product information. In retail store consumer be able to check food product detail especially expire date and in case of food issues happen supplier easly identified source of product. Beside identification and product safety, delivery can be monitoring by agent as every bucket tagged by an RFID tag. By using this system benefit for the consumer, supplier and authority for identification and monitoring system.